2020
DOI: 10.3389/fimmu.2020.00625
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 Implication in M1 Polarization and the Impact in Inflammatory Diseases

Abstract: Macrophages are known to have an impact in cytokine signaling in the myriad of organs in which they reside and are classically known to be either pro-inflammatory (M1), anti-inflammatory (M2). Different classes of signaling molecules influence these states, of which, microRNAs represent key modulators. These are short RNA species approximately 21 to 23 nucleotides long that generally act by binding to the 3 untranslated region of mRNAs, regulating their translation, and, thus, the quantity of protein they enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 79 publications
0
24
0
Order By: Relevance
“…For example, miR-155 is considered to target and silence c-Fos expression, thus playing an essential role in dendritic cell maturation [ 54 ]. miR-155 regulates macrophage polarization, by inhibiting the M1 pro-inflammatory phenotype, alongside the TGF-β signaling pathway, with a significant negative impact on the restorative and protective role of M2 macrophages [ 55 ].…”
Section: Research Directions Investigating Hhv-6 Involvement In Alzhe...mentioning
confidence: 99%
“…For example, miR-155 is considered to target and silence c-Fos expression, thus playing an essential role in dendritic cell maturation [ 54 ]. miR-155 regulates macrophage polarization, by inhibiting the M1 pro-inflammatory phenotype, alongside the TGF-β signaling pathway, with a significant negative impact on the restorative and protective role of M2 macrophages [ 55 ].…”
Section: Research Directions Investigating Hhv-6 Involvement In Alzhe...mentioning
confidence: 99%
“…However, researchers have not determined whether BMAL1 participates in the pathological processes of brain injury after ICH. (15) and participates in various pathological mechanisms, including oxidative stress and inflammation (16)(17)(18). Through a gene sequencing analysis, the GCAUUAA sequence was found to be present in the 3' untranslated region of BMAL1.…”
Section: Introductionmentioning
confidence: 99%
“…This result might indicate the role of M1 macrophages in the process of RA pathogenesis (51,70). Besides, Kurowska Stolarska et al revealed that miR-155 expression level is upregulated in synovial macrophages and monpcytes of patients diagnosed with RA.…”
Section: Rheumatoid Arthritismentioning
confidence: 93%